Fibre optic interconnect devices and passive components. Basic test and measurement procedures. Examinations and measurements. Spring compression force of the coupling sleeve for rectangular ferrule multi-fibre connectors Part 3-48, (30th September 2013) - British Standards Institution,
No abstract available